Cardio vascular risk profile among diabetic patients attending a tertiary care hospital in Odisha, India - Patro, Shubhransu; Kande, Sushant; Deo, Dandi Suryanarayana; Pathi, Debasis; Arora, Sidharth; Acharya, Swastik (International Journal of Advances in Medicine, 2019)
Background: Diabetes is associated with reduced quality of life and wide range of complications including CVD which vary geographically. The likely causes for the dramatic increase in the CVD rates include lifestyle changes associated with urbanization and the epidemiologic as well as nutritional transitions that are associated with economic development. This study aims to identify the CVD risk factors that exists among the diabetes patients of Odisha. Methods: The study was conducted in KIMS during July-December 2016. A total of 300 diabetic and 300 non-diabetic patients were included in the study. Medical history and lifestyle data were collected using a pretested structured format and a separate checklist for laboratory results. Patient interview, physical examination and laboratory analysis were performed. Chi-square test was performed to identify significance of difference between prevalence of risk factors between diabetic and non-diabetic groups. Multiple logistic regression analyses (forward stepwise addition) were performed to identify the variables significantly associated with CVD risk factors. Significance level of 5% was considered. Results: Total 376 males and 224 females were enrolled in the study with higher proportion of male participants in both diabetic and non-diabetic groups. Overall mean age of study subjects was 47.5±10.4 years. No significant difference was observed for demographic distribution between both groups. Prevalence of dyslipidaemia among diabetic patients was 86%, while prevalence of hypertension and dyslipidaemia were 71% and 62.3% respectively. Conclusions: Overall prevalence of CVD risk factors observed in this study among population of Odisha, is higher compared to reported prevalence for other regions of India.